MMT Effects on Gasoline Vehicles: A Literature Review - Hoekman, S. Kent; Broch, Amber (SAE International journal of fuels and lubricants, 2016)
Methylcyclopentadienyl manganese tricarbonyl (MMT) is an octane-boosting gasoline additive that has been used for over 50 years. This usage has been controversial; particularly in modern gasoline vehicles equipped with advanced emissions control systems. There is concern that extended use of MMT will lead to build-up of Mn-containing deposits on engine and emissions system components, thereby adversely affecting vehicle emissions performance and durability. This paper provides a comprehensive review of the literature regarding the effects of MMT on gasoline vehicles, with an emphasis on modern, Tier 2 vehicles. Numerous test programs have been conducted - including wide ranges of vehicle model years, technology types, and testing conditions. The reported MMT effects over this body of literature are not consistent. In general, studies by automakers have concluded that under certain test conditions, use of MMT is detrimental; contributing to catalyst plugging, deteriorated performance, and increased emissions. In contrast, most studies by Ethyl/Afton have concluded that under typical operating conditions, use of MMT does not cause harm, and does not contribute to exceedances of vehicle emissions standards. These opposing conclusions can be attributed largely to two factors: (1) differences in test cycles/conditions and (2) the basis for emissions comparisons. To achieve compliance with stringent Tier 2 emissions standards, automakers have adopted more active catalysts having higher cell densities, higher surface areas, and thinner cell walls. Furthermore, these catalysts are mounted in configurations that are close coupled (CC) to the exhaust manifold, promoting more rapid initial heating and higher overall catalyst temperatures. These technology enhancements have increased concerns about the use of MMT. There is credible evidence that under certain in-use operating conditions, MMT has contributed to catalyst plugging in Tier 2 vehicles. Similar concerns are expected to apply to future Tier 3 technology vehicles.